2014
DOI: 10.3390/nu7010253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Riboflavin Intakes and Status of 20–64-Year-Old Adults in South Korea

Abstract: A recent Korea National Health and Nutrition Survey indicated inadequate riboflavin intake in Koreans, but there is limited research regarding riboflavin status in South Korea. The purpose of this study was to determine riboflavin intake and status of Korean adults. Three consecutive 24-h food recalls were collected from 412 (145 men and 267 women) healthy adults, aged 20–64 years, living in South Korea and urine samples were collected from 149 subjects of all subjects. The dietary and total (dietary plus supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Riboflavin (vitamin B 2 ) is a water-soluble vitamin that is involved in a number of oxidative enzyme systems in electron transport (161). Flavin mononucleotide and flavin adenine dinucleotide are riboflavin coenzymes involved in diverse redox reactions in human metabolism and work as electron carriers (162) in carbohydrate, lipid, and other B vitamins and drug metabolism (163).…”
Section: Riboflavinmentioning
confidence: 99%
“…Riboflavin (vitamin B 2 ) is a water-soluble vitamin that is involved in a number of oxidative enzyme systems in electron transport (161). Flavin mononucleotide and flavin adenine dinucleotide are riboflavin coenzymes involved in diverse redox reactions in human metabolism and work as electron carriers (162) in carbohydrate, lipid, and other B vitamins and drug metabolism (163).…”
Section: Riboflavinmentioning
confidence: 99%
“…A systematic review including data from adults ≥65 years ( n 28 000) in Europe, North America, Australia and New Zealand concluded that 41 % of males and 31 % of females had dietary intake values below the estimated average requirement, with riboflavin identified as one of six nutrients considered to be a possible public health concern ( 56 ) . Similarly in Asia, a number of large population-based studies and national dietary surveys have reported inadequate riboflavin intakes ( 57 59 ) . It has been suggested that the Chinese population tend to excrete very little riboflavin and thus their requirement may be lower than that of other populations ( 60 ) ; however, this requires further investigation.…”
Section: Riboflavin Status: the Global Picturementioning
confidence: 99%
“…Riboflavin deficiency is prevalent in many regions over the world, particularly in underdeveloped countries with a low intake of dairy products and meats5678. In the clinical conditions, patients with certain types of cancers and congenital heart disease, as well as those with excessive alcohol intake, are at a greater risk of riboflavin deficiency9.…”
mentioning
confidence: 99%